Optimized Strategies for Managing Abdominal Hydatid Cysts and Their Complications - Alin Mihetiu; Dan Bratu; Dan Sabau; Octavian Nastase; Alexandra Sandu; Ciprian Tanasescu; Adrian Boicean; Cristian Ichim; Samuel Bogdan Todor; Dragos Serban; Adrian Hasegan (Diagnostics, 2024)
Hepatic hydatid cysts are an example of a zoonosis with global distribution, but with endemic characteristics in certain geographic areas. Known since ancient times, this parasitic infection predominantly affecting the liver and lungs remains a challenge today in terms of diagnosis and the pharmacological, radiological, endoscopic, or surgical therapy. This study analyzed the complications associated with different procedures for treating hydatid cysts in 76 patients admitted to the County Clinical Emergency Hospital of Sibiu. Complications occurred in 18 patients (23.7%), with no significant correlation to age, gender, or residency (urban or rural). Patients undergoing open surgery exhibited the highest complication rate (61.1%) compared to those treated with other procedures. The most frequent complication was biliary duct rupture, occurring in 22.7% of cases. Our findings indicate that the presence of complications significantly prolongs hospitalization time [t df (75) = 12.14, p < 0.001]. Based on these findings, we conclude that the surgical approach for hydatid cysts should be meticulously tailored to each patient’s specific circumstances to reduce the risk of complications and improve clinical outcomes.